2012
DOI: 10.1002/etc.2022
|View full text |Cite
|
Sign up to set email alerts
|

Protective and antioxidant role of selenium on arsenic trioxide–induced oxidative stress and genotoxicity in the fish hepatoma cell line PLHC‐1

Abstract: In vitro models are useful tools for rapid screening for toxicity, elucidation of mechanisms of toxicity, and understanding complex interactions among environmental toxicants. These evaluations may provide useful information for ecological evaluations if the relationship between in vitro and in vivo effects is established. The present study was undertaken to evaluate the protective effect of selenium on arsenic trioxide (As(2) O(3) )-induced cytotoxicity, DNA damage, and apoptosis. N-acetylcysteine (NAC), a fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 35 publications
2
23
0
1
Order By: Relevance
“…In cells incubated in the presence of As 2 O 3 (100 μM -IC 50 concentration for 10, 20 or 40 h) decreased GPx activity was observed. After 10 and 20 h, in cells preincubated with selenium (1, 5 or 10 μM) for 2 h this effect was alleviated by all doses, whereas after 40 h the higher doses proved to be entirely ineffective [6].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In cells incubated in the presence of As 2 O 3 (100 μM -IC 50 concentration for 10, 20 or 40 h) decreased GPx activity was observed. After 10 and 20 h, in cells preincubated with selenium (1, 5 or 10 μM) for 2 h this effect was alleviated by all doses, whereas after 40 h the higher doses proved to be entirely ineffective [6].…”
Section: Discussionmentioning
confidence: 91%
“…The outcomes of research on its possible protective properties against prooxidative processes have seemed to be promising and encouraging. Inorganic selenium (sodium selenite) has been found to prevent oxidative stress caused by methamphetamine in neuronal cells [5] and by As 2 O 3 in fish hepatoma cells [6], as well as t-butyl hydroperoxide-induced DNA damage in human mesenchymal stromal cells [7]. Other forms (organic compounds and nanoparticles) of selenium have also been studied and the research has revealed the dependence of the effects on the used form [3,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium is known to produce DNA damage and lipid peroxide in vitro and in vivo as well as selenium provides a protective effect against cadmium induced genotoxicity (Hurná et al, 1997). Selenium has ability to increase glutathione peroxidase activity in the elimination of peroxide radicals, thereby providing significant protection against genotoxicity of chemical that induced oxidative DNA damage and apoptosis in aquatic organism (Selvaraj., et al 2012). Cadmium chloride induced their genotixicity through the induction of oxidative stress, while melatonin reduces this effect by detoxification of oxygen and nitrogen-based free radicals and related non-radical products (Jahangir et al 2006;Reiter et al, 2007Reiter et al, , 2010.…”
Section: Resultsmentioning
confidence: 99%
“…합물은 반응산소종(reactive oxygen species, ROS) 생 성과 세포독성을 증가시켰고, 항산화물질들은 비소에 의 한 산화스트레스 효과를 억제시켰다 (Cha et al, 2006;Soria et al, 2010;Selvaraj et al, 2012). 또한, 동물실 험에서 비소화합물은 간 독성과 간 지질과산화를 촉진시 켰고, 혈중 및 간 GSH 수준을 감소시켰으며, 반면에 페 놀성 화합물은 비소에 의한 독성효과를 억제시켰다고 보 고된 바 있어 (Gao et al, 2013), 비소의 독성효과는 적어 도 산화스트레스에 의한 것으로 알려져 있다.…”
Section: 임태진unclassified